Osteohistology of Rapetosaurus krausei (Sauropoda: Titanosauria) from the Upper Cretaceous of Madagascar. Issue 4 (4th July 2018) - Curry Rogers, Kristina; Kulik, Zoe
Abstract: Titanosauria is a clade of sauropod dinosaurs that includes species ranging from the largest known terrest-rial vertebrates to insular dwarfs no bigger than elephants. Although most sauropod dinosaurs exhibit highly vascularized fibrolamellar bone signaling rapid growth rates comparable to those of extant mammals, diminutive titanosaurs apparently exhibit histological traits consistent with reduced primary growth rates and/or truncated active growth to reach small adult body sizes. A better understanding of the evolution of titanosaur body size requires additional sampling of the 40+ known titanosaur species. The best-preserved and most complete titanosaur yet discovered is Rapetosaurus krausei from the Maastrichtian Maevarano Formation in Madagascar. Skeletal material from many individuals spanning a wide range of ontogeny, from neonates to very large body sizes, makes Rapetosaurus an ideal candidate for an analysis of growth. We analyzed Rapetosaurus histology using a growth series of 25 forelimb, hind limb, and girdle elements representing different ontogenetic stages, including samples from the largest Rapetosaurus known (femur length = 143  cm). Primary bone histology in Rapetosaurus is highly vascularized fibrolamellar tissue, such as is found in other sauropods and most sampled titanosaurs. Secondary remodeling begins early, as noted in other titanosaur taxa, and by mid-ontogeny is pervasive in most sampled elements. The largest known Rapetosaurus was still growing, whereas some small juveniles exhibit an unusual pattern of bone erosion and replacement in the context of peripheral lines of arrested growth that signal a temporary pause in bone apposition. We hypothesize that these signals may relate to the drought-stressed ecosystem inhabited by Rapetosaurus . Citation for this article: Curry Rogers, K., and Z. Kulik. 2018. Osteohistology of Rapetosaurus krausei (Sauropoda: Titanosauria) from the Upper Cretaceous of Madagascar. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2018.1493689.